Wine science : principles and applications - Jackson, Ron S. (Elsevier, AP, 2014)
"With its three previous best-selling editions, Wine Science has proven to be an extensive account of the three central tenets of wine science: grape cultivation, wine production, and wine assessment. This fourth edition presents the latest updates on current wine production methods in a framework that explains the use, as well as the advantages and disadvantages of alternate procedures. Ronald Jackson's wealth of experience is matched by his ability to effectively communicate, making this book ideal for those seriously interested in the science of wine as well as professionals, professors and students."--Resumé vydavatele
Keywords: víno; vinohradnictví; vinařství; výroba vína; wine; viticulture; wine making; monografie; elektronické knihy; monographs; electronic books